Power development in professional rugby players. - Huw R Bevan (2011)
The ability to develop high levels of muscular power is considered an essential component of success in many sporting activities. Currently, a number of training methods exist aimed at developing muscular power such as training at the optimal load for Peak Power Output (PPO) and complex training, however to date there is no real consensus as to the most effective way of implementing these training modalities into elite sport. The aim of the first experiment was to determine the optimal load for PPO during the Jump Squat, Bench Press Throws and Hang Power Clean in a group of professional rugby players. This was achieved by comparing the PPO at various loads of the subject's predetermined estimated 1 RM in a randomised and balanced order for Hang power cleans, (HPC) Bench Press Throws (BBT) and Jump Squats (JS). The results of this study indicate that relative intensity had a significant effect on PPO during the HPC, BBT and the JS and that peak values were obtained in our athletes when working against an external load that was equivalent to 80% IRM in the HPC, 30% 1 RM in the BBT and with BM only in the JS. The second experiment aimed to determine the required recovery time for maximal benefits between the heavy resistance training (HRT) and subsequent upper and lower body explosive performance in a group of professional rugby players. Twenty professional rugby players performed a countermovement jump (CMJ) at baseline and -15 s, 4, 8, 12, 16, 20 and 24 min following a HRT bout (3 sets of 3 repetitions 87% IRM of Squat). Power output (PO), jump height and peak rate of force development (PRFD) were determined for all countermovement jumps. Performance increased significantly following 8 min recovery between the HRT and the CMJ (p < 0.001) (e.g. jump height increased by 4.9 +/- 3.0 %). The results of this experiment demonstrate that muscle performance during a CMJ can be significantly enhanced following bouts of HRT providing adequate recovery (?8 min) is given between the HRT and the explosive activity. The aim of the final experiment was to determine the effect of PAP on sprint performance in professional rugby players. Sixteen professional male rugby players performed five, 10 m sprints (with 5 m split): baseline, 4, 8, 12 and 16 min after the preload stimulus (1 set of 3 repetitions of the back squat at 91% IRM). No significant time effect over the duration of the study with regard to 5 m and 10 m sprint times. However, when individual responses to PAP were taking into account a significant improvement in sprint performance was observed over both 5 and 10 m compared to the baseline sprint. The results of this experiment indicate that sprinting performance is enhanced following a pre-load stimulus providing adequate and individualised recovery is given between the two activities. This may have important implications for training speed.